Tax Compliance Dynamics: The Role of Trust, Perception of Power, and Tax Knowledge in Taxpayers - Haryadi, Deni; Hidayah, Nurul (Al-Makki Publisher, 2025)
This study aims to analyze the influence of trust and power perception on taxpayer compliance in the Jabodetabek area and to examine the moderating role of tax knowledge as a moderating variable. A quantitative approach was employed using a survey method. A total of 350 questionnaires were analyzed using the sampling approach by Hair et al., and the data were processed using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results show that trust in tax authorities significantly affects tax compliance, indicating that greater trust leads to higher compliance. Conversely, power perception does not significantly influence compliance, suggesting that perceived authority alone does not directly impact taxpayer behavior. Tax knowledge strengthens the relationship between both trust and power perception with compliance. The study’s practical implication is that tax authorities should emphasize education and trust-based strategies rather than relying solely on authoritative approaches to enhance tax compliance.